Penyelesaian Problem Gaussian Elimination Menggunakan Posix Thread, Open MP dan Intel TBB - Ari Wibowo (JURNAL INTEGRASI, 2014)
Improved performance of the computer itself is not only utilize the processor alone, but could use the current GPU speed can exceed the processor though. This increase was also intended that in one instruction, the computer can directly handle the various processes at once without deadlock. The most commonly used way is to use a thread. The use of threads can improve performance up to thousands of times compared to the serial computation.